2016
DOI: 10.1021/acs.jafc.6b03897
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Ochratoxin A: Role for a Carbon-Linked C8–Deoxyguanosine Adduct?

Abstract: Ochratoxin A (OTA) is a fungal toxin that is considered to be a potent kidney carcinogen in rodent models. The toxin produces double strand breaks and has a propensity for deletions, single-base substitutions, and insertions. The toxin reacts covalently with DNA to afford a C8-2'-deoxyguanosine carbon-linked adduct (OT-dG) as the major lesion in animal tissues. Incorporation of model C-linked C8-aryl-dG adducts into the G3 site of the NarI sequence demonstrates a tendency to induce base substitutions and delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Molecular dynamics (MD) simulations on damaged DNA is a useful approach for gaining structural insights into the role of adduct formation in the associated mutagenicity. Specifically, MD simulations permit the study of DNA structural dynamics, which can be further used to explain experimental observations. Therefore, as a first step toward understanding the impact of OTA exposure on DNA structure, we previously employed MD simulations to characterize the conformational preferences of DNA containing the OT-G adduct. , The adduct was paired against complementary cytosine in a DNA oligomer containing the Nar I recognition sequence (5′-G 1 G 2 CG 3 CC), which is the known hotspot for mutations induced by other carcinogenic C 8 -G adducts . Our analysis revealed that OTA-damaged DNA likely adopts a mixture of three distinct (i.e., the major groove (B), wedge (W), and base-displaced intercalated (S)) conformations (Figure B–D) regardless of the adduct ionization state and the lesion-site sequence context.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations on damaged DNA is a useful approach for gaining structural insights into the role of adduct formation in the associated mutagenicity. Specifically, MD simulations permit the study of DNA structural dynamics, which can be further used to explain experimental observations. Therefore, as a first step toward understanding the impact of OTA exposure on DNA structure, we previously employed MD simulations to characterize the conformational preferences of DNA containing the OT-G adduct. , The adduct was paired against complementary cytosine in a DNA oligomer containing the Nar I recognition sequence (5′-G 1 G 2 CG 3 CC), which is the known hotspot for mutations induced by other carcinogenic C 8 -G adducts . Our analysis revealed that OTA-damaged DNA likely adopts a mixture of three distinct (i.e., the major groove (B), wedge (W), and base-displaced intercalated (S)) conformations (Figure B–D) regardless of the adduct ionization state and the lesion-site sequence context.…”
Section: Introductionmentioning
confidence: 99%
“…There are various health benefits of sleep, including the maintenance of many cellular processes and memory-related function [142]. With aging, sleep quality also decreases and inferior sleep quality is usually related to many age-associated neurodegenerative diseases like AD and PD [98] which are further associated with failure of proteostasis network that brings a question that whether there is any direct correlation of proteostasis with sleeping behavior.…”
Section: Sleeping Behavior and Proteostasis: Rest Is The Basis Of Activitymentioning
confidence: 99%
“…The quality of sleep changes across the healthy aging process. In general, as humans reach maturity, some studies suggest that sleep need decreases (Manderville and Wetmore, 2017). Across aging, there are key changes in sleep architecture.…”
Section: Aging: Effects On Sleep and Protein Homeostatic Regulationmentioning
confidence: 99%
“…While the specific functions of sleep are still actively researched, some benefits of sleep, including memory consolidation (Stickgold and Walker, 2007; Diekelmann and Born, 2010) and management of cellular processes (Benington and Heller, 1995; Cirelli et al, 2004), have been demonstrated. However, it is known that sleep quality decreases with age (Manderville and Wetmore, 2017) and poor sleep is often a symptom of many aged-related neurodegenerative diseases, such as Alzheimer’s disease (AD; Ju et al, 2013). This begs the question to what extent is sleep causally related to the progression of aging and the symptoms of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%